Introduction to Philosophy Philosophy of Mind (Open textbook library., 2019)
Introduction to Philosophy: Philosophy of Mind surveys the central themes in philosophy of mind and places them in a historical and contemporary context intended to engage first-time readers in the field. It focuses on debates about the status and character of the mind and its seemingly subjective nature in an apparently more objective world.